Alzheimer’s Disease: Erythrocyte 2,3-diphosphoglycerate Content and Circulating Erythropoietin - Järemo, Petter; Jejcic, Alenka; Jelic, Vesna; Shahnaz, Tasmin; Behbahani, Homira; Oweling, Magnus; Winblad, Bengt (Current Alzheimer Research, 2019)
Background: Alzheimer’s Disease (AD) features the accumulation of β-amyloid in erythrocytes. The subsequent red cell damage may well affect their oxygen-carrying capabilities. 2,3- diphosphoglycerate (2,3-DPG) binds to the hemoglobin thereby promoting oxygen release. It is theorized that 2,3-DPG is reduced in AD and that the resulting hypoxia triggers erythropoietin (EPO) release. Methods & Objective: To explore this theory, we analyzed red cell 2,3-DPG content and EPO in AD, mild cognitive impairment, and the control group, subjective cognitive impairment. Results: We studied (i) 2,3-DPG in red cells, and (ii) circulating EPO in AD, and both markers were unaffected by dementia. Disturbances of these oxygen-regulatory pathways do not appear to participate in brain hypoxia in AD.
Keywords: erythrocytes